Polyphenols could be Effective in Exerting a Disinfectant-Like Action on Bioprosthetic Heart Valves, Counteracting Bacterial Adhesiveness - Naso, Filippo; Calafiore, Antonio Maria; Gaudino, Mario; Zilla, Peter; Haverich, Axel; Colli, Andrea; Melder, Robert John; Gandaglia, Alessandro (Cardiology and Cardiovascular Medicine, 2022)
Background: The incidence of infective endocarditis in patients with bioprosthetic heart valves is over 100 times that of the general population with S. aureus recognized as the causative organism in approximately 1/3 of cases. In this study, (1) the microbicidal and virucidal effect of a polyphenolic solution was carefully evaluated. The same solution was then adopted for the treatment of a commercial bioprosthetic heart valve model for (2) the assessment of inhibition of S. aureus adhesiveness. Methods: (1) the viability of 9 microorganisms strains (colony-forming units) and the infectivity degree of 3 viral strains (cellular infection capacity) were evaluated after suspension in the polyphenolic solution. (2) Leaflets from a treated and untreated commercial surgical valve model were incubated with a known concentration of S. aureus. After incubation, the leaflets were homogenized and placed in specific culture media to quantify the bacterial load. Results: (1) The polyphenolic solution proved to be effective in eliminating microorganisms strains guaranteeing the killing of at least 99.9%. The effectiveness is particularly relevant against M. chelonae (99.999%). (2) The polyphenol-based treatment resulted in the inhibition of the S. aureus adhesiveness by 96% concerning untreated samples. Conclusions: The data suggest an interesting protective effect against infections and bacterial adhesiveness by a polyphenolic-based solution. Further studies will plan to extend the panel of microorganisms for the evaluation of the anti-adhesive effect; however, the use of optimized polyphenolic blends could lead to the development of new treatments capable to make transcatheter-valve substitutes more resistant to infection.